EKSTRAK DAUN KECAPI SEBAGAI INHIBITOR KOROSI BAJA DALAM MEDIUM ASAM KLORIDA - Sari Wahyuni; Emriadi Emriadi; Suryati Suryati (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2022)
Kecapi (Sandoricum koetjape, (Burm.f.) Merr) leaf extract contains secondary metabolites such as alkaloids, flavonoids, phenolics and triterpenoids which may be an environmentally friendly corrosion inhibitor. The method used in extraction of kecapi leaves in 1 N hydrochloric acid as a steel corrosion inhibitor was carried out by weight loss, FTIR (Fourier Transform Infrared) and SEM (Scanning Electron Microscopy) methods. The data from the weight loss method revealed that the rate was inversely proportional to the concentration of the inhibitor and directly proportional to the temperature, while the value of the efficiency inhibition was directly proportional to the temperature and concentration of the inhibitor. The maximum efficiency inhibition value obtained was 86.61% at an extract concentration of 6 g/L and an immersion temperature of 60oC. The adsorption of kecapi leaf extract followed the Langmuir adsorption isotherm.